In vitro and in vivo activation of L-serine deaminase in Escherichia coli K-12. - Newman, E B (1985)
Escherichia coli L-serine deaminase (L-SD) in crude extracts made in glycylglycine could be activated by incubation with iron sulfate and dithiothreitol. This activation could also be demonstrated in vitro in two mutants which were physiologically deficient in L-SD activity in vivo. This suggests that these mutants were deficient not in L-SD but in an enzyme(s) activating L-SD. The suggestion is made that production of a functional L-SD in vivo requires activation of the structural gene product by an enzyme or enzymes that reduce the protein to an active form.